Academic Senate Recording 2015-05-14 - Academic Senate:::::::::
This recording was digitized from cassette tapes. Chair Report. Agenda Approved. Minutes of 4/30 approved. Consent items: French Language for Wine Business certificate, Revision to the Biochemistry Bachelor's of Science program – Approved. President Report. Senate Budget Subcommittee Report. FSAC Report. Election of At-Large Senators to Executive Committee. Human Development Revision approved. EPC Report. Direct Entry Masters in Nursing Discontinuance approved. Provost Report. Associated Students Report. Staff Report. Proposal for changing the formula for representatives on the Senate and duties of Senators approved for vote. Changing of the Guard. Good of the Order.